Kritik Hadis: Pemikiran Kritis Aḥmad Amīn - Bustamin Bustamin (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2004)
This article reviews Ahmad Amin's thoughts on hadith. Based on the book “Fajr al-Islām,” seven aspects of hadith criticism are found, namely the absence of codification, fabrication of hadiths, reasons for the fabrication of hadiths, efforts by scholars to rectify the fabrication and the steps they take through various means, prominent figures in hadith, efforts made for the codification of hadiths, and the treasury of hadiths in the dissemination of culture. These are the seven aspects of hadith criticism criticized by Amin in “Fajr al-Islām”.